Prostate Cancer - Faustino, Ana; Oliveira, Paula A. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The prostate is the largest accessory gland of the male reproductive tract. Together with seminal vesicles and bulbourethral glands, the prostate is responsible for the production of an alkaline fluid that forms part of the seminal fluid. The prostates of men over 40 years of age are commonly affected by several pathologies, such as benign prostate hyperplasia and cancer. Prostate cancer is one of the most frequently occurring cancers among men population worldwide. According to the World Health Organization (WHO), in the year 2018, prostate cancer affected approximately 1.28 million men and was responsible for the death of 358,989 of them. Prostate cancer development is associated with several risk factors, such as older age, black ethnicity, a family history of disease, an increased body mass index and obesity. In this way, the risk of prostate cancer development may be reduced through the consumption of a healthy diet full of fruits and vegetables, practice of physical exercise and maintenance of a healthy weight.Despite several approaches being available for prostate cancer treatment, the number of prostate cancer deaths is continuously increasing, which emphasizes the need to search for new methods for precocious diagnosis and more effective treatment. Animal models, including rodents, have greatly contributed to the study of biopathology and the prevention and treatment of prostate cancer.This Special Issue presents original research works, case reports and reviews concerning the diagnosis, treatment and prognosis of prostate cancer, highlighting new advances in this field.